أثر التوجه الاستراتيجي في الأداء المؤسسي في المؤسسات الخدمية بولاية الخرطوم - احمد محمد علي, الطاهر (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة الي معرفة أثر التوجه الاستراتيجي في الأداء المؤسسي في المؤسسات الخدمية بولاية الخرطوم، وتم بناء نموذج الدراسة استنادا على الادبيات السابقة. استخدمت الدراسة المنهج الوصفي لتحقيق اهداف الدراسة. حيث وزعت (390) استبانة للمدراء، استرد منها (370) بنسبة (94.9%)، والصالحة للتحليل عدد (345) بنسبة (88.5%). وقد توصلت الدراسة الي مجموعة من النتائج أهمها: توجد علاقة بين الأداء المؤسسي والتوجه الإبداعي بينما لا توجد علاقة بين الأداء المؤسسي وتوجه المنافسين والعملاء. تم مناقشة النتائج مع الدراسات السابقة، ومن ثم تقديم عدد من التوصيات والمقترحات. The study aimed to know the impact of strategic direction on institutional performance in service institutions in the state of Khartou, and the study model was built on the basis of previous literature. The study used the descriptive approach to achieve the objectives of the study. Where (390) questionnaires were distributed to managers, of which (370) were recovere, at a rate of (94.9%), and (345) were valid for analysis, at a rate of (88.5%). The study reached a set of results, the most important of which are: There is a relationship between institutional performance and creative orientation, while there is no relationship between institutional performance and the orientation of competitors and customers. The results were discussed with previous studies, and then a number of recommendations and suggestions were presented
The Impact of Strategic Direction on Institutional Performance in Service Institutions in The State of Khartoum
مقال
Keywords: التوجه نحو الابداع، التوجه نحو العملاء، التوجه المؤسسي، الأداء المؤسسي; Keywords: Orientation towards performance, Orientation towards clients, Institutional orientation, Institutional performance.